Nitrogen metabolism of sheep and goats consuming Acacia brevispica and Sesbania sesban - Woodward, A.; Reed, J.D. (Oxford University Press, 1997)
We described the effects of two East African browses, Acacia brevispica and Sesbania sesban, on nitrogen metabolism of sheep and goats. The A. brevispica had a substantial amount of proanthocyanidins (condensed tannins); S. sesban did not. The browses were fed at three levels in combination with vetch (Vicia dasycarpa) and teff straw (Eragrostis abyssinica). Fecal N, N balance, and plasma urea N (PUN) were estimated with intact animals. Ruminal ammonia (RuA) and VFA concentrations were estimated with ruminally fistulated animals. Urinary N loss, PUN, RuA and VFA concentrations were higher for S. sesban diets than for A. brevispica diets. Fecal N was highest with diets including A. brevispica due to high levels of fecal neutral-detergent insoluble N. Nitrogen retention was highest for diets including S. sesban. Nitrogen retention was adequate for A. brevispica diets because low urinary N compensated for high fecal N. Four hypotheses describe possible effects of tannis on N metabolism: 1) escape of protein from the rumen to the lower tract; 2) increased microbial yield; 3) increase in N-containing endogenous products; and 4) protein made indigestible in tannin-protein complexes. The effect of tannins in A. brevispica on N metabolism can best be described by the formation of indigestible tannin-protein complexes, although increased production of endogenous products is also possible.